The influence of sintering temperature on the properties of compacted bovine hydroxyapatite - Herliansyah, M.K.; Abd Shukor, Mohd Hamdi; Ide-Ektessabi, A.; Wildan, M.W.; Toque, J.A. (Elsevier, 2009)
On the sintering characteristic of hydroxyapatite (HA), the resulting microstructure and properties are influenced not only by the characteristic and impurities of materials but also are found to be dependent on the thermal history during the fabrication process. This research is concerned with the effect of sintering temperature on the relative density, hardness, and phase purity after sintering process. Bovine HA (BHA) powder obtained from heated local cortical bovine bone at 900 degrees C for 2 h was uniaxially pressed at 156 MPa into green bodies using a 20 mm cylindrical dies. The compacted green body was pressurelessly sintered in air atmosphere at temperatures ranging from 1000 to 1400 degrees C, at a furnace ramp rate of 5 degrees C/min and dwell time of 2 h. The BHA starting powder was characterized using XRD and FTIR SEM was also used for observing the microstructures of the starting material. The sintered BHA specimens were analyzed using Archimedes method for measuring density; XRD for phase stability; and Vickers method for hardness measurement. The analysis results show that the starting BHA powder and the sintered BHA specimens contain HA. The intensity of the three main peaks of HA decreases with increasing sintering temperature which may be due to decomposition of HA at high temperature. The density and hardness of BHA increases with increasing sintering temperature based on the results obtained. (C) 2009 Elsevier B.V. All rights reserved.